Transformasi Fungsi SDM : Redefinisi Peran Dan Dampak Dalam Organisasi - Bugie Zurisdianto Pamungkas; Vip Pramarta; Aji Argo Putro; Shelly Ayu Andesty; Basrudin Basrudin; Ripka Margaretha Ponggele (Universitas 45 Surabaya, 2023)
Organizational Challenges Transformation of the HR function and redefinition of the role of HR has become an important issue in the modern business context. Rapid and complex changes in the business environment, advances in technology, globalization, and changes in employee preferences and expectations have driven organizations to change the way they view and manage human resources. In this journal or article, we discuss the importance of transforming the HR function and redefining the role of HR in facing modern organizational challenges. Background, we explain the factors that underlie the need for transformation of the HR function, such as technological changes, globalization, demographic changes, and changes in organizational paradigms. We also outline the goals of this transformation, including increasing organizational competitiveness, efficiency, employee experience, and organizational capacity. Implementation, we discuss the steps that need to be taken by organizations to implement the transformation of the HR function. This involves planning a clear strategy, engaging leaders in leading change, providing relevant training and development, and measuring and evaluating the success of the transformation. Our conclusion highlights the importance of transforming the HR function and redefining the role of HR in facing the challenges of modern organizations. In this ever-changing era, organizations must change their paradigm in managing human resources in order to utilize the full potential of their human resources. The transformation of the HR function brings benefits such as increased competitiveness, efficiency, employee experience and organizational capacity. Thus, it is important for organizations to take the necessary steps to implement this transformation in order to achieve long-term success.